Level of professional functioning visual artists depending on the type of reasons for choosing a profession - Witold Adamczyk; Anna Podolak; Joanna Jarczak; Tadeusz Ambroży (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
Interest in the topic comes from empirical observations of various professional groups and people operating within particular professions. An extremely interesting phenomenon is the diversity of attitudes towards the profession. Extremely negative, reluctant attitudes on the one hand, up to full fascination and delight on the other are observed. Relatively least common is a strong and positive commitment to the profession, treating work not only as a financial necessity or fate, but as a joy. There are people who would not change their profession to any other, and a retrospective analysis of experience allows us to reach statements about great satisfaction with the chosen profession type of work or type of activity. Assuming that the status of a master in the artist's profession determines the personality traits of young people interested in artistic activity, knowledge of the essential features of the biographies of several dozen professionally and environmentally verified artists in Poland and Germany allows for the creation of a model for implementing the process of shaping a personality that functions positively in this type of professions.